2021
DOI: 10.4269/ajtmh.20-0829
|View full text |Cite
|
Sign up to set email alerts
|

Role of Abandoned and Vacant Houses on Aedes aegypti Productivity

Abstract: The control of container Aedes species by house inspections usually achieves insufficient coverage and impact because a percentage of residents are absent and some residents refuse inspections and treatments. In addition, another fraction of the buildings may be uninhabited, such as those for rent or sale, or abandoned. Although the productivity of Aedes aegypti has been investigated in abandoned lots, less is known about the importance of uninhabited buildings. We investigated Ae. aegypti pupal productivity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…However, the latter study opened the way to test new technological tools to obtain higher resolution photos that generated stronger entomological results. In addition, drones can be a surveillance tool to identify breeding sites in inaccessible areas of the home, such as roofs, and in closed houses and vacant lots; this is due to the importance of monitoring these areas of mosquito populations [31]. This is particularly the case in areas with COVID-19 cases, where health personnel should not be in contact with inhabitants [15,32].…”
Section: Discussionmentioning
confidence: 99%
“…However, the latter study opened the way to test new technological tools to obtain higher resolution photos that generated stronger entomological results. In addition, drones can be a surveillance tool to identify breeding sites in inaccessible areas of the home, such as roofs, and in closed houses and vacant lots; this is due to the importance of monitoring these areas of mosquito populations [31]. This is particularly the case in areas with COVID-19 cases, where health personnel should not be in contact with inhabitants [15,32].…”
Section: Discussionmentioning
confidence: 99%
“…Through our formative research activities, we found that residents’ migration resulting in more abandoned houses [ 60 ]—which in turn increases the number of mosquito breeding sites on these properties—was a concern for community residents, and creates a challenge for effective mosquito surveillance and control in this area. These findings, along with results of entomological surveillance conducted in the area confirmed a high mosquito population in Ponce, stressing the need to test and use new mosquito control methods for Ae .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies in PR showed higher productivity of Ae. aegypti in lower-income neighborhoods where discarded containers were more abundant than in middle-income neighborhoods (Barrera et al 2021). Acknowledging socio-economic differences in Ae.…”
Section: Discussionmentioning
confidence: 99%